Utilização das recomendações para profilaxia de transmissão vertical do HIV - Almeida, Bruna Lígia Ferreira (2013)
The feminization of the epidemic have many consequences, among them, the increasing number of HIV-infected children with mother to child transmission as the main route of infection. In 2010, the Ministry of Health created the recommended prophylaxis manual of mother to child HIV transmission and antiretroviral therapy in pregnant women and other behaviors related to prevention of mother to child HIV transmission. The objective of this study was to analyze if the recommendations of the Ministry of Health as control of mother to child HIV transmission are being taken by pregnant women and health professionals of a public maternity hospital in Goiânia. Research conducted between March and May 2012, divided into two stages: cross-sectional study, which consisted in the analysis of medical records of 323 HIV positive pregnant women seen at a public hospital in the State of Goiás between years 2006 to 2011, and second it is cross-sectional study involving 25 professionals working in maternity and obstetric center of this institution. Among the 323 records analyzed, 48.9% of pregnant women were included in the age group between 25 to 34 years old, 68.7% were single, 65.6% brown, 50.5% had study time between 4-7 years and 74.9% were unemployed. We checked the main risks related to mother to child HIV transmission in the 323 analyzed records. Among of the professionals surveyed, 76% have inadequate knowledge about HIV testing in pregnant women, 80% unaware the gestational age in what is realized elective caesarean, 66% do not know the dose to attack AZT and the elapsed time before child-birth, 84% do not know which method is indicated for lactation inhibition. The data observed in our study are alarming and show gaps in care for HIV positive pregnant women and newborns exposed, through information obtained that contradict this practice.